Hangman's Beautiful Daughter - McCrumb, Sharyn (Maxwell Macmillan, 1992)
Summoned to the scene of a ghastly crime in her remote Appalachian village, Laura Bruce, the new minister's wife, realizes that Sunday school teacher Nora Crumb's dark visions have come true.
Keywords: Mystery